Kefir and the Gut–Skin Axis - Alves, Emília; Gregório, João; Rijo, Patrícia; Rosado, Catarina; Monteiro Rodrigues, Luis (International journal of environmental research and public health, 2022)
The human gastrointestinal (GI) tract is a dynamic system influenced by various environmental factors, including diet and exposure to ingested probiotics, and prone to various functional impairments. These impairments are mostly related to any combination of motility alterations, visceral hypersensitivity, and changes in the mucosa, immune function, and intestinal microbiota. Intestinal microbial imbalance and immunological dysfunction have been linked to several chronic inflammatory disease states, including atopic dermatitis (AD). Disruption of the intestinal microbial balance, known as gut dysbiosis, has been demonstrated to negatively impact skin function by increasing the intestinal permeability. Consequently, the gut–skin axis may be receptive to modulation via dietary modification, namely, via ingestion of probiotics, thus representing interesting potential as an AD therapy. Kefir is an ancient probiotic food that has been demonstrated to positively impact the general condition of the digestive system, including the intestinal microbiota. However, the literature is still scarce on the impact on the gut–skin relationship of a diet containing kefir. This study, continuing research in our group, aimed to evaluate the impact of kefir intake on GI symptoms in healthy and AD skin subjects. Results showed a significant improvement in GI status, namely, in functional constipation, abdominal pain intensity, and abdominal distension, thus supporting the hypothesis that kefir intake is positively associated with improvement in GI status. The existence of a relationship between the improvement in skin parameters and the improvement in GI status after kefir consumption was established, thus reinforcing the role of homemade kefir as a potential modulator of the gut–skin axis in both healthy and atopic individuals.